Using TRIZ Theory to Solve the Problem of Structural Innovation of Gear Operating Mechanism - Hu Yuzhou; Han Jiahua (Jixie chuandong)
The gear operating mechanism is one of the core components of the vehicle and the main control carrier for the operation of the vehicle. As the traditional gear operating mechanism has some defects such as single function,complicated operation and limited scope,a new structure design plan is created by related tools of TRIZ after a deeply research of TRIZ in its theory and method system,which makes the new mechanism a great advantage in volume,function,universality,reliability and other aspects. Ultimately,the purpose of accomplishment of the core structure design and optimization of product performance is achieved. Compared with the existing products, the new gear mechanism has characteristics of smaller volume, higher functional integration,higher reliability and better versatility.